Myth as Urban Collective Memory: A Reading of José María Arguedas’s Representation of Cuzco in "Los Ríos Profundos" - Maxwell Woods (Mitologías Hoy)
This article explores the socio-political function of mythical representations of urban space in Latin American literature. Based on an analysis of the first chapter of José María Arguedas’s Los ríos profundos (1958), I argue that myth is a narrative technology of collective memory that binds together a regional community through the practice of reproducing shared narratives of the urban meaning of a uniting city. More precisely, I look at the function of the myth of Cuzco as the “center of the world” in the opening chapter of Arguedas’s novel.